Asymptomatic Malaria among Blood Donors in Benin City Nigeria - ONAIWU TOLA OHIENGBOMWAN (My University, 2014)
Background: This study aimed at determining the prevalence and associated risk factors for asymptomatic malaria parasitaemia and anemia among blood donors in a private medical laboratory in Benin City, Nigeria. Methods: Venous blood was collected from a total of 247 blood donors. Malaria status, ABO, Rhesus blood groups and hemoglobin concentration of all participants were determined using standard methods. Results: The prevalence of asymptomatic malaria infection was higher among commercial blood donors than volunteer group (commercial vs. volunteer donor: 27.5 %vs. 13.8%; OR = 2.373, 95% CI = 0.793, 7.107, P = 0.174). Asymptomatic malaria was not significantly affected by gender (P = 0.733), age (P = 0.581), ABO (P= 0.433) and rhesus blood groups (P =0.806) of blood donors. Age was observed to significantly (P = 0.015) affect malaria parasite density with donors within the age group of 21-26 years having the highest risk. The prevalence of anemia was significantly higher among commercial donors (commercial vs. volunteer donors: 23.4% vs. 3.4%: OR = 8.551, 95% CI = 1.135, 64.437, P = 0.013) and donors of blood group O type (P =< 0.0001). Conclusions: Asymptomatic malaria parasitaemia and anemia was higher among commercial donors than voluntary donors. Mandatory screening of blood donors for malaria parasite is advocated to curb transfusion transmitted malaria and associated sequelae.